Downregulation of Plzf Gene Ameliorates Metabolic and Cardiac Traits in the Spontaneously Hypertensive Rat - Liška, František; Landa, Vladimír; Zídek, Václav; Mlejnek, Petr; Šilhavý, Jan; Šimáková, Miroslava; Strnad, Hynek; Trnovská, Jaroslava; Škop, Vojtěch; Kazdová, Ludmila; Starker, Colby G; Voytas, Daniel F; et al. (Hypertension (Dallas, Tex., 2017)
The spontaneously hypertensive rat (SHR), one of the most widely used model of essential hypertension, is predisposed to left ventricular hypertrophy, myocardial fibrosis, and metabolic disturbances. Recently, quantitative trait loci influencing blood pressure, left ventricular mass, and heart interstitial fibrosis were genetically isolated within a minimal congenic subline that contains only 7 genes, including mutant Plzf (promyelocytic leukemia zinc finger) candidate gene. To identify Plzf as a quantitative trait gene, we targeted Plzf in the SHR using the transcription activator-like effector nuclease technique and obtained SHR line harboring targeted Plzf gene with a premature stop codon. Because the Plzf targeted allele is semilethal, morphologically normal heterozygous rats were used for metabolic and hemodynamic analyses. SHR-Plzf+/- heterozygotes versus SHR wild-type controls exhibited reduced body weight and relative weight of epididymal fat, lower serum and liver triglycerides and cholesterol, and better glucose tolerance. In addition, SHR-Plzf+/- rats exhibited significantly increased sensitivity of adipose and muscle tissue to insulin action when compared with wild-type controls. Blood pressure was comparable in SHR versus SHR-Plzf+/-; however, there was significant amelioration of cardiomyocyte hypertrophy and cardiac fibrosis in SHR-Plzf+/- rats. Gene expression profiles in the liver and expression of selected genes in the heart revealed differentially expressed genes that play a role in metabolic pathways, PPAR (peroxisome proliferator-activated receptor) signaling, and cell cycle regulation. These results provide evidence for an important role of Plzf in regulation of metabolic and cardiac traits in the rat and suggest a cross talk between cell cycle regulators, metabolism, cardiac hypertrophy, and fibrosis.
Keywords: alely; esenciální hypertenze; metabolismus lipidů; Kruppel-Like Transcription Factors; transcriptome; Promyelocytic Leukemia Zinc Finger Protein; Essential Hypertension; Blood Pressure Determination; Lipid Metabolism; Hypertension; Down-Regulation; kardiomyocyty; Fibrosis; fibróza; analýza rozptylu; Blotting, Western; hypertrophy, left ventricular; protein promyelocytické leukemie s motivem zinkového prstu; Alleles; krysa rodu Rattus; Analysis of Variance; hypertrofie levé komory srdeční; Hypertrophy, Left Ventricular; Phenotype; fibrosis; zvířata; Myocytes, Cardiac; Cells, Cultured; hypertension; down regulace; Quantitative Trait Loci; Male; potkani inbrední SHR; hypertenze; fenotyp; kultivované buňky; rats, inbred SHR; stanovení celkové genové exprese; transkripční faktory Krüppel-like; Real-Time Polymerase Chain Reaction; Rats; Animals; Gene Expression Profiling; western blotting; mužské pohlaví; Rats, Inbred SHR; kvantitativní polymerázová řetězová reakce; měření krevního tlaku; lokus kvantitativního znaku